A Case Study on the Multimodal Coordinated Relationship of Teacher Scaffolding in a Content and Language Integrated Classroom - Liu, Shuqi; Zhao, Xiuyan; Sun, Xin (Journal of Educational Research and Policies, 2025)
This study uses a teaching video of a Content and Language Integrated (CLI) comprehensive English course, which is taught by an English major teacher in a certain university, as the corpus. The video is 80 minutes in length. Based on the constructed Framework of Systemic Functional Multimodal Discourse Analysis, it explores the application of teacher scaffolding, its multimodal characteristics, and how various modalities coordinate with scaffolding language to construct meaning. The research findings are as follows: (1) In the CLI classroom, the teacher employed a diverse range of teaching scaffolding to help students, mainly including reinforcing key information, guiding self-correction, bridging information gaps, and simplifying tasks; additionally, most of the teacher scaffolding activities are targeted at content, followed by language. (2) Teacher scaffolding exhibits distinct multimodal characteristics. The teacher predominantly uses falling tones, and frequently employs intonation nuclei to emphasize key points. Gestures mainly consist of stress gestures and symbolic gestures that help convey complex concepts. The teacher often moves around in the classroom space, and her eye movements mainly involve scanning the entire class; there are certain differences in the multimodal characteristics of the scaffolding used by the teacher when focusing on different aspects. (3) The various modalities of teacher scaffolding coordinate with scaffolding language to jointly construct the ideational meaning, interpersonal meaning, and textual meaning of teacher scaffolding. They often form a complementary and reinforcing relationship (primary-secondary and expansion) with scaffolding language. This study aims to provide some insights for CLI teachers on how to construct teacher scaffolding and achieve effective classroom teaching.